ANALISIS BEBAN KERJA PEGAWAI PADA KANTOR PELAYANAN PERBENDAHARAAN PONTIANAK - Liliyana, Liliyana; Abdullah, Abdullah; Azaria, Elsa (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2022)
This study aims to determine Employee Workload at the Pontianak State Treasury Service Office and the impact of workload on employees and the solutions that can be provided. The researcher’s initial observations indicate that there is an excessive workload at the Pontianak Treasury Service Office can cause a decrease in employee word performance. The researcher uses descriptive quantitative methods with descriptive statistics. Data collection techniques were carried out through interviews, observation, and documentation studies. The researcher chooses the conversion staff, validator, and reviewers. The results of the analysis of the workload of employees in the Fund Disbursement Section, it is considered to exceed the specified workload. This can be seen from the results of the workload analysis calculation using the task-by-task position approach method, obtained the workload for the Conversion Executing Staff is 266,960 minutes, the Validator Implementing Staff is 277,772 minutes, and the Reviewer Implementing Staff is 292,232 minutes. The total volume of workload exceeds the effective working time in one year, which is 89,770 minutes. Excessive workload makes employees have to use time out of working hours. Suggestions need to be balanced with rewards in the form of compensation, a better transfer/promotion system, and the provision of facilities and rewards. This is in line with Bambang Agus Diana and Ridho Hartas’s research entitled Employee Workload Analysis at the UPBJJ Office-Universitas Open Bandung with the results of the uneven distribution of employee workload causing employee performance to decline.